Equal contributions of feline immunodeficiency virus and coinfections to morbidity in African lions. (December 2021) - Broughton, Heather; Govender, Danny; Serrano, Emmanuel; Shikwambana, Purvance; Jolles, Anna
Abstract: Feline immunodeficiency virus (FIV) is a pathogenic lentivirus related to human and simian immunodeficiency viruses that has been associated with AIDS-like pathologies in domestic and wild cats, as well as in hyenas. Despite known pathologies, progressive immunosuppression and ill health effects driven by these lentiviruses in association with other secondary infections remain understudied in free-ranging species. Here, the role of coinfections by gastrointestinal parasites and tick-borne hemoparasites for FIV disease progression was explored in 195 free-ranging African lions ( Panthera leo ) living in Kruger National Park (KNP), South Africa. Using statistical methodology, we evaluated the effects of FIV on a range of health indicators to explore how direct and indirect effects of FIV and associated coinfections align to determine lion health outcomes. Findings show direct negative effects of FIV on host immunity and nutritional status, and exacerbation of aggressive behaviors, conditions which may increase exposure/susceptibility to other secondary infections. When taken together, the contribution of coinfecting parasites to morbidity in lions is of similar magnitude as direct effects of FIV infection alone, suggesting that the particular coinfection assemblage may play a role in mediating disease progression within natural lion populations. Highlights: Immunosuppression by FIV increases richness and abundance of secondary parasites. Infection by gastrointestinal parasites drives severe malnourishment in FIV hosts. Hemoparasite infection contributed to liver pathology and clinical wasting. Contributions of secondary infections to morbidity equal the direct effects of FIV.